PH-sensitive CAP/SiO2 composite for efficient co-delivery of doxorubicin and siRNA to overcome multiple drug resistance. Issue 8 (27th January 2020) - Cai, Zheng; Chen, Yuezhu; Zhang, Yingwen; He, Zhimei; Wu, Xiaoge; Jiang, Li-Ping
Abstract : CAP/SiO2 composite with good biocompatibility and acid biodegradability has been prepared. The proposed drug and gene codelivery system based on it demonstrated enhanced therapeutic efficacy for multiple drug resistance cells. Abstract : Long-term administration of chemotherapeutic agents often leads to multiple drug resistance (MDR), which greatly impairs the treatment outcome. To overcome this problem, a biodegradable nanocarrier based on an acid-sensitive calcium phosphate/silica dioxide (CAP/SiO2 ) composite was constructed for the codelivery of drug and siRNA. Anticancer drug doxorubicin (DOX) was encapsulated into the composite scaffold by interacting with the exposed Ca 2+ of CAP/SiO2 to achieve high drug loading (180 μg mg −1 ). With further decoration of siRNA, the nanocarrier was applied to enhance the therapeutic efficacy by silencing MDR-relevant genes (P-gp) of DOX-resistance K562/ADR cancer cells. Benefiting from the intrinsic acid degradability of CAP/SiO2, the nanocomposite demonstrated pH-responsive release behavior, favoring drug/siRNA release within acidic endo-/lysosomes. Consequently, due to the drug and gene effects, this biodegradable nanomedicine demonstrated enhanced therapeutic efficiency, providing a novel strategy for cancer therapy.